From Nucleic Acids Sequences to Molecular Medicine - Erdmann, Volker A.; Barciszewski, Jan (RNA Technologies, 2012)
For this RNA Technologies volume a world-wide outstanding group of RNA specialists are contributing the most recent developments in this fast moving field of RNA molecular biology. The book features up-to-date information of our current knowledge on antisense, ribozyme, micro RNA, and DNAzyme strategies, as well as on other small RNAs from eukaryotes and prokaryotes, and the employment of chemical modifications to stabilize ribonucleic acids for their use in living cells. This volume is not only excellent reading for the expert in the field of RNA technologies, but also for those interested in entering this field as a chemist, molecular biologist or as a medical doctor interested in RNA therapeutics of the future.